JEJAK KARBON KONSUMSI LPG DAN LISTRIK PADA AKTIVITAS RUMAH TANGGA DI KOTA DENPASAR, BALI - Made Wiratama, I Gusti Ngurah; Sudarma, I Made; Adhika, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 10 No 1 (2016)DO - 10.24843/EJES.2016.v10.i01.p11, 2016)
Every one of us uses carbon dioxide emitting energy source in our daily activities. The purposes of this research were to obtain information on the level of household activities of carbon footprint and to obtain information on the most influential factor of household activities in Denpasar City. The research method employed was the descriptive quantitative. The analysis of the first purpose was obtained by the multiplication of emission factor and the use of LPG and electrical capacity. The analysis of the second purpose was obtained by implementing the analysis of doubled linier regression supported by employing SPSS version 16.00 program for Windows. The research result showed that the average of the total carbon footprint was as big as 138,037.02 g of carbon/month. Based on that average, the total of carbon footprint in Denpasar city with as many as 15,908 households was 2,195.89 ton CO2e/month. The statistic analysis test showed the factors that influenced the carbon footprint were the amount of household members, the amount of household equipments which needed LPG to operate, the amount of household equipments which needed electricity to operate and the duration of using electric equipments whose R2 power was as big as 90%. The duration of using electric equipments had the highest correlation with the value of 62.70 %. It is suggested that households should use energy saving equipments such as LED products; the government should consistently promote carbon saving movements; and to future research to calculate carbon footprint by using DNPI carbon calculator, or by using software LEAP.
Keywords: Carbon footprint, electricity and LPG consumptions, household